A meta-analysis of targeted interventions for reducing suicide-related behaviour and ideation in adolescents: Implications for trial design - Keith Gaynor; Maeve Dwan O'Reilly; David Redmond; Ciara Nealon; Conal Twomey; Eilis Hennessy (Comprehensive Psychiatry, 2023)
Introduction: Suicidality among young people is a significant societal issue. The current study conducted a meta-analysis of community and clinical interventions targeting suicide attempts, self-harm, and suicidal ideation in adolescents. Methods: Interventions targeting suicide attempts, self-harm and suicidal ideation were identified by searching PsychINFO, Medline, CINAHL and Embase in line with the PRISMA statement. Study quality was determined using a risk of bias tool. Meta-analyses examined the efficacy of the interventions. Effect sizes were calculated for suicidal ideation data (continuous data) using Hedge's g for standardised mean differences. Suicide attempts and self-harm (dichotomous data) were calculated using odds ratios (ORs). Results: Seventeen RCTs were included in the meta-analysis. No significant differences were found between treatment and control groups on measures of suicide attempts or self-harm. A small effect-size was observed on measures of suicidal ideation (g = 0.47). A secondary meta-analysis investigated change over time in treatment as usual conditions, finding significant large effect-sizes for suicide attempts (OR = 18.67), self-harm (OR = 12.77), and suicidal ideation (g = 0.86). Limitations: The methodological decision to focus on specific outcomes over a broad definition of self-harm excluded some papers, which have been included in other reviews. It is unlikely to have significantly affected the overall results. The review was not preregistered. Conclusions: These twin findings highlight the importance overcoming the methodological difficulty of discerning effective interventions during a period of baseline improvement. We suggest that future trials should move away from broadly addressing “suicidality/self-harm” and encourage a greater targeting of at-risk individuals.